2013
DOI: 10.2196/jmir.2829
|View full text |Cite
|
Sign up to set email alerts
|

The Good, Bad, and Ugly of Online Recruitment of Parents for Health-Related Focus Groups: Lessons Learned

Abstract: BackgroundWe describe our experiences with identifying and recruiting Ontario parents through the Internet, primarily, as well as other modes, for participation in focus groups about adding the influenza vaccine to school-based immunization programs.ObjectiveOur objectives were to assess participation rates with and without incentives and software restrictions. We also plan to examine study response patterns of unique and multiple submissions and assess efficiency of each online advertising mode.MethodsWe used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 18 publications
1
55
1
Order By: Relevance
“…In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different. Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different. Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 studies that did not find social media to be the best method, 7 studies were interventional studies [18-21,24,25,40], whereas 8 were observational studies [23,27,33-35,37-39]. Of these studies, 3 studies specifically targeted young and middle-aged adults [24,25,40], 2 studies targeted adolescents [34,37], and 2 studies targeted older adults [35,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As 70 % of the overweight or obese women in the sample who were not currently attempting weight loss reported that they were at least somewhat interested in a Twitterdelivered weight loss intervention, our study provides insights into interest among women who would benefit from weight loss (i.e., overweight and obese women), regardless of current motivation to lose weight. We did not confirm that respondents' IP addresses were unique, thus leaving open the possibility that women completed the survey more than once [48]. However, participants received no compensation for participation, thus reducing the likelihood of duplicate responses.…”
Section: Original Researchmentioning
confidence: 96%